Development of a PMSM motor field-oriented control algorithm for electrical vehicles - Ramesh, P.; Umavathi, M.; Bharatiraja, C.; Ramanathan, G.; Athikkal, Sivaprasad (Materials today : proceedings, 2022)
Recently, with issues such as global warming, melting of glaciers and climate change, the need for sustainable methods of living has seen a drastic increase. Combustion cars that run on petrol and diesel are slowly being replaced with electrical vehicles (EVs). Currently, EVs face challenges in terms of range of kilometers offered, availability of charging systems, infrastructure for their development, etc. As the need for electrical vehicles increase, the usages of Permanent Magnet Synchronous Motor (PMSM) too have seen a growing trend. Motor control in an electrical vehicle is extremely crucial as a vehicle on road is subject to different terrains and hence, different loads. Throughout all these different scenarios, it is essential that the motor operates at its optimum efficiency in order to provide optimum vehicle performance for the driver and passengers. Currently, several methods are available for the control of electrical vehicles, nevertheless the field-oriented control (FOC) method for permanent magnet motors is widely used due to its efficient nature. This paper discusses with the design of modified FOC control algorithm for control the PMSM motor eliminates an initial jerk seen during the starting condition of a motor thereby providing a smoother start. As the entire simulation is done using Hardware in the Loop model, the values obtained have real life constraints taken into account, as opposed to a software only simulation. Moreover, the transient time taken to reach a steady state value in speed and to also change direction of rotation have been improved as well. The simulation has been designed entirely on the Altair Embed software.